Data flow : visualising information in graphic design. - Klanten, Robert, 1964- (Berlin : Gestalten, 2006)
The application of diagrams extends beyond its classical field of use today. Data Flow charts this development, introduces the expansive scope of innovatively designed diagrams and presents an abundant range of possibilities in visualising data and information. These range from chart-like diagrams such as bar, plot, line diagrams and spider charts, graph-based diagrams including line, matrix, process flow, and molecular diagrams to extremely complex three-dimensional diagrams. Data Flow is an up-to-date survey providing cutting-edge aesthetics and inspirational solutions for designers, and at the same time unlocks a new field of visual codes...